Distinct binding sites on HLA-DR for invariant chain and staphylococcal enterotoxins. - Karp, D R (1992)
During biosynthesis, class II molecules of the major histocompatibility complex exist as complexes of the polymorphic alpha and beta chains in association with trimers of the invariant chain (Ii). The nonpolymorphic Ii contains sequences necessary for proper targeting of class II to endosomal compartments, where Ii is degraded. Ii also prevents the premature association of antigenic peptides with class II molecules. It is not known whether the effect of Ii on peptide binding extends to other ligands of class II, specifically exogenous superantigens. Cells expressing a mutant Ii molecule stably associated with HLA-DR at the cell surface were tested for their ability to interact with staphylococcal toxins. Most toxins (staphylococcal enterotoxins A-E and exfoliative toxin) were found to bind to cells expressing this alpha beta Ii complex with levels comparable to cells expressing only alpha beta chains at the cell surface. Cells expressing surface alpha beta Ii complexes stimulated polyclonal populations of peripheral blood T cells in association with these toxins. Binding of toxic shock syndrome toxin (TSST) and subsequent stimulation of T cells were reduced by the presence of the Ii. This reduction was not due to an alteration in the repertoire of T cells responding to TSST in the presence of Ii. Data from experiments with a T-cell clone suggest that interactions between class II molecules and T-cell antigen receptors occur during staphylococcal enterotoxin-mediated stimulation and that surface Ii does not interfere with such interactions.